1994
DOI: 10.1139/t94-040
|View full text |Cite
|
Sign up to set email alerts
|

State-boundary surface for very loose sand and its practical implications

Abstract: A state-boundary surface defines a boundary in stress -void-ratio space above which no stress state can exist. The applicability of the state-boundary surface for sand has not gained widespread attention primarily because sand is not generally considered to be a difficult soil from a design point of view apart from liquefaction. Liquefaction is a phenomenon usually encountered in very loose cohesionless materials. An experimental study relating the drained and undrained behavior of very loose saturated sand is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(19 citation statements)
references
References 14 publications
4
15
0
Order By: Relevance
“…Tensile stresses and strains are considered as positive in the model simulation in order to maintain consistency throughout the paper. The simulation results are in close agreement with the experimental data reported by Sasitharan et al (1994) and Carraro (2006). The values of the CASM model parameters for Ottawa sand are given in Table 1.…”
Section: Sand Constitutive Model Casmsupporting
confidence: 90%
“…Tensile stresses and strains are considered as positive in the model simulation in order to maintain consistency throughout the paper. The simulation results are in close agreement with the experimental data reported by Sasitharan et al (1994) and Carraro (2006). The values of the CASM model parameters for Ottawa sand are given in Table 1.…”
Section: Sand Constitutive Model Casmsupporting
confidence: 90%
“…Many have postulated that the breakdown of a metastable structure in loose soils in association with excessive volume changes during loading ultimately leads to collapse and liquefaction. Important works by Castro (1969), Casagrande (1936Casagrande ( , 1976, Seed and Idriss (1969), Bishop (1971Bishop ( , 1973, Castro and Poulos (1977), Poulos, (1981), Poulos et al (1985), Sladen et al (1985), Vaid and Chern, (1985); Alarcon-Guzman et al (1988), Negussey et al (1988), Kramer and Seed (1988), Vasquez-Herrera et al (1988), Konrad (1993), Sasitharan et al (1993), Sasitharan et al (1994), Lade and Pradel (1990), Sassa (1985Sassa ( , 2000, Sassa et al (2003), and Wang and Sassa (2002) bear witness to the extent of research and interest in soil liquefaction.…”
Section: Introductionmentioning
confidence: 99%
“…Chern (1983) [16], Kramer and Seed (1988) [17], Vasquez-Herrera and Dobry (1989) [18], Lade (1992) [19], (1993) [20], Ishihara (1993) [21], Konrad (1993) [22], Sasitharan et al (1993) [23], (1994) [24] and among others) identified similar yield conditions and proposed various names for these conditions. The collapse line is considered as a limit state boundary between the stable and the unstable states of soil undrained behaviour.…”
Section: Undrainedmentioning
confidence: 99%